Guia sobre vacinação segura na atenção básica: convergências para educação permanente em saúde - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
The immunization is considered in public health as one of the most effective strategies in the prevention and control of immunopreventable diseases. The nursing needs to afford appropriate skills and tools that corroborate for safe vaccination practices. OBJECTIVE: To develop, together with nursing professionals from the National Immunization Program of the Municipal Health Department of Manacapuru, Amazonas a technological health product for the promotion of permanent education about safe vaccination. METHODOLOGY: qualitative study, based on Convergent Care Research, realized in the city of Manacapuru, Amazonas. Participated in the study six nurses and 13 nursing technicians with experience in immunization. The data collection took place in November 2020, through the Focus Group technique, as a convergence space. RESULTS: they are presented by means of two scientific articles and a Technological Product. ARTICLE 1- Integrative literature review, searching databases. Having with PICO – P: Nursing Professionals; I: Education Process in service/permanent/continuing; C: does not apply, since the comparison between care was not sought; O: use of educational technology in immunization, in the period from 2014 to 2019. Included three articles, publisheds in Brazil, in Kenya, in the United States and in Canada. The technologies used were: Update Course, training DVD, online course. The english language predominated in most articles. The review showed scarcity of publications relevant to the use of educational technologies related to the qualification of nursing workers focused on training on immunization. ARTICLE 2 - sought to identify, from the perspective of nursing professionals, Continuing Education in the context of safe vaccination, through a descriptive, qualitative study. In the data collection, was used a semi-structured instrument, containing open questions about the contributions of the educational experiences about immunization, being analyzed through the content analysis of Bardin. Emerged three categories: “Distancing the nurse in the routine of the vaccination room”; “Nursing technicians as protagonists in the vaccine room”; ”Continuing education as a tool for training nursing professionals in the field of immunization and its subcategories: lack of knowledge about safe vaccination to ensure the quality of care in the vaccination room and lack of adherence of nursing professionals) in the face of training in immunization. It is concluded that the little participation of nurses in the management of immunization actions can contribute to weakening the safe process in the practice of immunization. It becomes relevant the develop a guiding instrument for continuing education in immunization, considering the complexity of procedures related to nursing practice in immunization in the regional context of Amazonas. TECHNOLOGICAL PRODUCTION – Guide for strengthening Continuing Education about Safe Vaccination. It was developed together with the nursing professionals participating in the research, it will ensure the quality of health care in the context of immunization, as recommended by the Unified Health System. Prepared based on the results of the Integrative Literature Review, in spaces of convergence with the research subjects, in consultation with the guiding documents of national and international health agencies. CONCLUSION: Through the Convergent Care Research methodology, it was possible to build a Guide about safe vaccination for the Permanent Education Service of the Department of Health of the Municipality of Manacapuru, Amazonas, a Process Technology that will be a guide for the assistance and management practices of the nursing in the immunization process. The spaces of convergence of PCA are made explicit by the juxtaposition of practice with scientific investigation, concretized by dialogued exchange between professionals and researchers. It is expected that further studies are developed, as this is a topic of great global relevance in the control and promotion of vaccine-preventable diseases. The instrument will be validated in future researches.
Guide on safe vaccination in primary care: convergences for permanent health education
Keywords: Enfermeiros de saúde pública; Manacapuru (AM); Enfermeiro e paciente; Enfermeiros - Treinamento; Guia profissional; CIÊNCIAS DA SAÚDE; Tecnologia educacional; Educação permanente; Imunização; Vacinação; Enfermagem; Segurança do paciente